Early inhibition of endothelial retinoid uptake upon myocardial infarction restores cardiac function and prevents cell, tissue, and animal death. (January 2019) - Danzl, Katarina; Messner, Barbara; Doppler, Christian; Nebert, Clemens; Abfalterer, Anna; Sakic, Adel; Temml, Veronika; Heinz, Katharina; Streitwieser, Robert; Edelmann, Thomas; Mairhofer, Mario; Grimm, Michael; et al.
Abstract: Physiologically, following myocardial infarction (MI), retinoid levels elevate locally in the infarcted area. Whereas therapeutic systemic application of retinoids was shown to reduce the progression of ventricular dilatation and the onset of heart failure, the role of acute physiologically increased retinoids in the infarction zone is unknown to date. To reveal the role of local retinoids in the MI zone is the central aim of this study. Using human cell culture and co-culture models for hypoxia as well as various assays systems, lentivirus-based transgene expression, in silico molecular docking studies, and an MI model in rats, we analysed the impact of the retinoid all-trans retinoic acid (ATRA) on cell signalling, cell viability, tissue survival, heart function, and MI-induced death in rats. Based on our results, ATRA-mediated signalling does aggravate the MI phenotype (e.g. 2.5-fold increased mortality compared to control), whereas 5′-methoxyleoligin (5ML), a new agent which interferes with ATRA-signalling rescues the ATRA-dependent phenotype. On the molecular level, ATRA signalling causes induction of TXNIP, a potent inhibitor of the physiological antioxidant thioredoxin (TRX1) and sensitizes cells to necrotic cell death upon hypoxia. 5ML-mediated prevention of ATRA effects were shown to be based on the inhibition of cellular ATRA uptake by interference with the cholesterol (and retinol) binding motif of the transmembrane protein STRA6. 5ML-mediated inhibition of ATRA uptake led to a strong reduction of ATRA-dependent gene expression, reduced ROS formation, and protection from necrotic cell death. As 5ML exerted a cardioprotective effect, also independent of its inhibition of cellular ATRA uptake, the agent likely has another cardioprotective property, which may rely on the induction of TRX1 activity. In summary, this is the first study to show i) that local retinoids in the early MI zone may worsen disease outcome, ii) that inhibition of endothelial retinoid uptake using 5ML may constitute a novel treatment strategy, and iii) that targeting endothelial and myocardial retinoid uptake (e.g. via STRA6 inhibition) may constitute a novel treatment target in acute MI. Highlights: Retinoids in the myocardial infraction zone have adverse effects on MI outcome. Inhibition of cellular retinoid uptake reduces cell death under hypoxic conditions. Endothelial cell death enhances cardiomyocyte death under hypoxic conditions. 5′-Methoxyleoligin inhibits cellular retinoid uptake by binding to STRA6. 5′-Methoxyleoligin protects from hypoxia and ATRA-enhanced cell death in MI.